The impact of Flexner's report on medical education in Sub-Saharan Africa Sudan as an example - Adam, Masoud I.; Eljac, Ibrahim A.; El-Ashkar, Ayman M. (International Journal Of Community Medicine And Public Health, 2024)
Flexner’s Report 1910 is one of the most important and influential events in the history of medicine worldwide that led to the emergence of modern medical education. reforms of medical education took places as results of this report leading to the establishment of the biomedical model as the gold standard of medical training. Objectives: to identify the impact of Flexner's Report on Medical Education in Sub-Saharan Africa taking Sudan as an example more than 100 years after the report. The health system and medical education in Sub-Saharan Africa during the colonial era and after independence were studied. Conclusion: Medical education in Sub-Saharan Africa has not yet received a holistic review, reforms, and standardization and the health system needs more educational strategic planning. Multiple factors play a role in preventing the modernization of medical education in Sub-Saharan Africa, such as the poor economic status of these countries, inadequate infrastructure, equipment, and educational standards, large annual students intake, and lack of appropriately qualified teaching staff.